Gastrointestinal Cryptococcosis Associated with Intestinal Lymphangiectasia - Fernando Naranjo-Saltos; Alejandro Hallo; Carlos Hallo; Andres Mayancela; Alejandra Rojas (Case Reports in Medicine)
Intestinal lymphangiectasia is a pathological dilation of enteric lymphatic vessels resulting in lymph leakage to the intestinal lumen. This chronic lymph leakage leads to a state of immunosuppression secondary to the loss of humoral and cellular components of the immune system and represents a potential risk factor for opportunistic infections. We report a case of protein-losing enteropathy in a seemingly immunocompetent patient. An intestinal histopathological study revealed the unusual association of lymphangiectasia and intestinal cryptococcosis. Although cryptococcal infection is common in immunocompromised patients, intestinal involvement is rarely reported. We found no reports on the association of intestinal cryptococcosis in patients with lymphangiectasia. This case report is the first to describe intestinal cryptococcosis associated with intestinal lymphangiectasia.